Global trends and prospects related to macrophage in chronic kidney disease: a bibliometric analysis - Yuxin Hu; Yaoxian Wang; Hanzhang Hong; Yexin Chen; Qinjie Zhou; Gegongming Zhu; Jingyi Tang; Weijing Liu; Lin Wang (Renal Failure)
Background and aims Macrophages play a variety of widely concerned roles in the process of chronic kidney disease (CKD). To further understand the research hotspots and development trends regarding the relationship between macrophages and CKD, the role of macrophages in the occurrence and progression of CKD was summarized by bibliometrics in this study.Material and Methods We collected the studies relevant the role of macrophages in CKD from the Web of Science Core Collection, which included 1332 relevant studies from Jan 1st, 2004 to Jul 6th, 2023 in WoSCC. CiteSpace, biblioshiny in R, VOSviewer and SCImago Graphica Beta were used for bibliometric analysis and visualization.Results Monash University from Australia is the most productive institution, while China and the USA are most productive countries. Anders HJ is the most cited author. In terms of the number of co-citations, the top one was “Macrophages: versatile players in renal inflammation and fibrosis” by Patrick Ming-Kuen Tang, published in Nature Reviews Nephrology in 2019. Important keywords of this research topic include inflammation, dendritic cell, oxidative stress, NF-κB, tgf-beta, interstitial fibrosis, glomerulonephritis, diabetic nephropathy. Future research hotspots may include molecular mechanism, acute kidney injury, macrophage polarization, kidney fibrosis.Conclusion This study provides a systematic review of the role of macrophages in CKD and speculates that future research hotspots. Previous studies have focused on the immune function of macrophages and atypia, and metabolic factors (especially iron metabolism within macrophages) have attracted the attention of researchers in recent years and are the forefront of recent research.